Canada, the International Criminal Court, and the intersection of international politics and finances. (June 2019) - Fisher, Kirsten J.; Sarkany, Laszlo
In 2018, Prime Minister Trudeau made two announcements regarding the International Criminal Court, both, it seems, aimed at reinforcing Canada's claim of human rights promotion and multilateralism: Canada declared Myanmar's actions against the Rohingya people genocide and urged the United Nations Security Council to refer the situation to the International Criminal Court, and it joined a collective referral of the Venezuela situation to the Court. As public measures of support, these are positive developments for the International Criminal Court, which has been suffering poor public relations and challenges to its legitimacy. However, Canada could do more by better supporting the financial viability of the Court. Currently, it aims to increase the Court's workload without supporting an increased budget, as reflected in Canada's involvement at the December 2018 Assembly of States Parties meeting. A seemingly sure way to undermine the International Criminal Court would be to add to its workload without ensuring it has the financial resources to do the work.